Liquid crystal display device
By using a specific in-plane phase retardation layer and a discontinuous emission spectrum backlight in a liquid crystal display device, the problems of visual clarity and color uniformity in a liquid crystal display device under strong light are solved, and excellent visual clarity and color reproduction under polarized optical components are achieved.
Patent Information
- Application Number
- CN202111189626.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2016-10-11
- Filing Date
- 2016-11-18
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2036-11-18
AI Technical Summary
When existing liquid crystal display devices are used under strong external light, the transmission axis direction of the polarized sunglasses and the transmission axis direction of the emission side of the liquid crystal display device are easily orthogonal to the Nicol's state, causing the screen to turn black and become impossible to visually confirm. At the same time, the use of λ/4 plates or ultra-high phase difference films can cause color unevenness and coloring problems.
A phase difference layer with a specific in-plane phase difference Re(550) of 100nm to 180nm is adopted, satisfying the relationship Re(450) < Re(550) < Re(650). The slow axis is configured at an angle of 35° to 55° with the long side of the liquid crystal panel. Combined with a backlight source with a discontinuous emission spectrum, it is ensured that the absorption axes of the first polarizer and the second polarizer are substantially orthogonal or parallel to the long side of the liquid crystal panel. A phase difference layer with a specific axis angle is used to suppress color unevenness.
It achieves excellent visual confirmation and color reproduction under polarized optical components, suppresses color unevenness, and is suitable for outdoor use.
Smart Images

Figure CN113917738B_ABST
Abstract
Description
[0001] This application is a divisional application of the invention patent with the application date of November 18, 2016, Chinese patent application number 201680069960.0, and invention name “Liquid Crystal Display Device” (International application No. PCT / JP2016 / 084246 entered the Chinese national stage). Technical Field
[0002] The present invention relates to a liquid crystal display device. Background Art
[0003] In recent years, the use of liquid crystal display devices under strong external light, such as mobile phones, smart phones, tablet personal computers (PCs), car navigation systems, digital signage, window displays, etc., has increased. When a liquid crystal display device is used outdoors as described above, when a visual confirmer wears polarized sunglasses to observe the liquid crystal display device, the transmission axis direction of the polarized sunglasses and the transmission axis direction of the exit side of the liquid crystal display device will become an orthogonal Nicol state according to the angle observed by the visual confirmer, resulting in a situation where the screen becomes black and the displayed image cannot be visually confirmed. In order to solve this problem, a technology of configuring a λ / 4 plate or an ultra-high phase difference film on the visual confirmation side of the liquid crystal display device has been proposed.
[0004] On the other hand, in order to improve the color reproducibility of liquid crystal display devices, attempts have been made to make the backlight source closer to the characteristics of individual red (R), green (G), and blue (B) light sources. However, even in such attempts, only arranging a λ / 4 plate or an ultra-high retardation film on the visual confirmation side of the liquid crystal display device as a countermeasure for polarized sunglasses still has the problem of coloration and / or color unevenness.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2005-352068
[0008] Patent Document 2: Japanese Patent Application Publication No. 2011-107198 Summary of the invention
[0009] Problems to be solved by the invention
[0010] The present invention has been made to solve the above-mentioned conventional problems, and an object of the present invention is to provide a liquid crystal display device having excellent color reproducibility, excellent visibility when viewed through an optical member having a polarizing effect, and suppressed color unevenness.
[0011] Means used to solve problems
[0012] The liquid crystal display device of the present invention comprises: a liquid crystal panel, which includes a liquid crystal unit, a first polarizer arranged on the visual confirmation side of the liquid crystal unit, and a second polarizer arranged on the back side of the liquid crystal unit; a phase difference layer, which is arranged on the visual confirmation side of the liquid crystal panel; and a backlight source, which illuminates the liquid crystal panel from the back side. The in-plane phase difference Re (550) of the phase difference layer is 100nm to 180nm, and satisfies the relationship Re (450) < Re (550) < Re (650). The angle between the slow axis of the phase difference layer and the long side of the liquid crystal panel is 35° to 55°. The backlight source has a discontinuous emission spectrum.
[0013] In one embodiment, the emission spectrum of the backlight source has a peak P1 in the wavelength region of 430nm to 470nm, a peak P2 in the wavelength region of 530nm to 570nm, and a peak P3 in the wavelength region of 630nm to 670nm. When the wavelength of peak P1 is set to λ1, the height is set to hP1, and the half-peak width is set to Δλ1, the wavelength of peak P2 is set to λ2, the height is set to hP2, and the half-peak width is set to Δλ2, the wavelength of peak P3 is set to λ3, the height is set to hP3, and the half-peak width is set to Δλ3, the height of the valley between peak P1 and peak P2 is set to hB1, and the height of the valley between peak P2 and peak P3 is set to hB2, they satisfy the following relationship equations (1) to (3):
[0014] (λ2-λ1) / (Δλ2+Δλ1)>1 (1)
[0015] (λ3-λ2) / (Δλ3+Δλ2)>1(2)
[0016] 0.8≤{hP2-(hB2+hB1) / 2} / hP2≤1 (3).
[0017] In one embodiment, the refractive index ellipsoid of the retardation layer shows a relationship of nx>nz>ny, and the Nz coefficient is 0.2 to 0.8.
[0018] In one embodiment, the liquid crystal display device further includes another retardation layer whose refractive index ellipsoid shows a relationship of nz>nx≥ny between the liquid crystal panel and the retardation layer.
[0019] In one embodiment, the backlight source includes a red LED (Light Emitting Diode), a green LED, and a blue LED, and the phosphor of the red LED is activated by tetravalent manganese ions. In another embodiment, the backlight source includes a blue LED and a wavelength conversion layer including quantum dots.
[0020] In one embodiment, the absorption axis of the first polarizer is substantially orthogonal or parallel to the long side of the liquid crystal panel, the absorption axis of the second polarizer is substantially orthogonal or parallel to the long side of the liquid crystal panel, and the absorption axis of the first polarizer is substantially orthogonal to the absorption axis of the second polarizer.
[0021] Effects of the Invention
[0022] According to an embodiment of the present invention, by using a backlight light source having a specific emission spectrum and arranging a phase difference layer having so-called reverse dispersion wavelength dependence and a specified in-plane phase difference at a specific axis angle on the visual confirmation side, a liquid crystal display device can be achieved that has excellent color reproducibility and excellent visual confirmation when visually confirmed through an optical component with a polarization effect, and color unevenness is suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic cross-sectional view of a liquid crystal display device according to one embodiment of the present invention.
[0024] Figure 2 This is a diagram schematically showing an example of an emission spectrum of a backlight light source that can be used in a liquid crystal display device according to an embodiment of the present invention.
[0025] Figure 3 This is a diagram schematically showing an example of an emission spectrum of a conventional backlight source. DETAILED DESCRIPTION
[0026] Hereinafter, representative embodiments of the present invention will be described, but the present invention is not limited to these embodiments.
[0027] (Definition of Terms and Symbols)
[0028] Definitions of terms and symbols in this specification are as follows.
[0029] (1) Refractive index (nx, ny, nz)
[0030] “nx” is the refractive index in the direction where the refractive index in the plane is maximum (ie, the slow axis direction), “ny” is the refractive index in the direction orthogonal to the slow axis in the plane (ie, the fast axis direction), and “nz” is the refractive index in the thickness direction.
[0031] (2) In-plane phase difference (Re)
[0032] "Re(λ)" is the in-plane phase difference of the film measured using light with a wavelength of λnm at 23°C. For example, "Re(450)" is the in-plane phase difference of the film measured using light with a wavelength of 450nm at 23°C. When the thickness of the film is set to d(nm), Re(λ) is calculated by the formula Re=(nx-ny)×d.
[0033] (3) Retardation in the thickness direction (Rth)
[0034] "Rth(λ)" is the phase difference in the thickness direction of the film measured using light with a wavelength of 550 nm at 23°C. For example, "Rth(450)" is the phase difference in the thickness direction of the film measured using light with a wavelength of 450 nm at 23°C. When the thickness of the film is set to d (nm), Rth(λ) is calculated by the formula Rth = (nx-nz) × d.
[0035] (4) Nz coefficient
[0036] The Nz coefficient is obtained by Nz=Rth / Re.
[0037] (5)nx=ny, nx=nz, ny=nz
[0038] nx=ny includes not only the case where nx and ny are completely identical but also the case where nx and ny are substantially identical. The same also applies to the relationship of nx=nz and ny=nz.
[0039] (6) Substantially orthogonal or parallel
[0040] The expressions "substantially orthogonal" and "substantially orthogonal" include the case where the angle formed by the two directions is 90°±10°, preferably 90°±7°, and more preferably 90°±5°. The expressions "substantially parallel" and "substantially parallel" include the case where the angle formed by the two directions is 0°±10°, preferably 0°±7°, and more preferably 0°±5°. Furthermore, the abbreviation "orthogonal" or "parallel" may also include the state of being substantially orthogonal or substantially parallel.
[0041] (7) Angle
[0042] In this specification, when an angle is mentioned, unless otherwise specified, the angle includes angles in both clockwise and counterclockwise directions.
[0043] A. Overall Structure of Liquid Crystal Display Device
[0044] Figure 1It is a cross-sectional schematic diagram of a liquid crystal display device of an embodiment of the present invention. In the figure, for the sake of convenience of observation, the ratio of the thickness of each layer and each optical component is different from that of the actual object. The liquid crystal display device 500 of this embodiment comprises a liquid crystal panel 100, a phase difference layer 200 arranged on the visual confirmation side of the liquid crystal panel 100, and a backlight light source 300 for illuminating the liquid crystal panel 100 from the back side. As for the example in the figure, another phase difference layer 400 may be further arranged between the liquid crystal panel 100 and the phase difference layer 200. Other phase difference layers may also be omitted depending on the purpose, structure, desired characteristics, etc. In addition, for the sake of convenience of explanation, the phase difference layer 200 is sometimes referred to as the first phase difference layer, and the other phase difference layer 400 is sometimes referred to as the second phase difference layer. With respect to the embodiment of the present invention, the in-plane phase difference Re (550) of the first phase difference layer 200 is 100nm to 180nm, preferably 110nm to 170nm, more preferably 120nm to 160nm, and particularly preferably 135nm to 155nm. Furthermore, the first retardation layer 200 satisfies the relationship of Re(450)<Re(550)<Re(650). In addition, in the embodiment of the present invention, the backlight source 300 has a discontinuous emission spectrum.
[0045] The liquid crystal panel 100 includes a liquid crystal unit 10, a first polarizer 20 disposed on the visual confirmation side of the liquid crystal unit 10, and a second polarizer 30 disposed on the back side of the liquid crystal unit 10. The absorption axis of the first polarizer 20 is substantially orthogonal or parallel to the long side of the liquid crystal panel 100 (liquid crystal unit 10). In addition, the absorption axis of the second polarizer 30 is also substantially orthogonal or parallel to the long side of the liquid crystal panel 100 (liquid crystal unit 10). In addition, the long side of the liquid crystal panel can be either the left-right direction or the up-down direction of the display screen. The absorption axis of the first polarizer 20 is substantially orthogonal to the absorption axis of the second polarizer 30. A protective film (not shown) may also be disposed on one side or both sides of the first polarizer 20. Similarly, a protective film (not shown) may also be disposed on one side or both sides of the second polarizer 30.
[0046] The angle formed by the slow axis of the first phase difference layer 200 and the long side of the liquid crystal panel 100 is 35° to 55°, preferably 38° to 52°, more preferably 40° to 50°, further preferably 42° to 48°, particularly preferably 44° to 46°, and particularly preferably about 45°. Therefore, the angle formed by the slow axis of the first phase difference layer 200 and the absorption axis of the first polarizer 20 is preferably 35° to 55°, more preferably 38° to 52°, further preferably 40° to 50°, particularly preferably 42° to 48°, particularly preferably 44° to 46°, and most preferably about 45°.
[0047] In one embodiment, a conductive layer (not shown) may be provided between the first polarizer 20 and the liquid crystal cell 10. By providing such a conductive layer, the liquid crystal display device can function as a so-called built-in touch panel type input display device in which a touch sensor is incorporated between the display cell (liquid crystal cell) and the polarizer.
[0048] Any appropriate optical compensation layer (another phase difference layer) may be arranged between the first polarizer 20 and the liquid crystal cell 10 and / or between the second polarizer 30 and the liquid crystal cell 10 as needed. The number, combination, arrangement position, arrangement order, optical properties (e.g., refractive index ellipsoid, in-plane phase difference, thickness direction phase difference, Nz coefficient), mechanical properties, etc. of such optical compensation layers may be appropriately set according to the purpose, the structure of the liquid crystal display device, and the desired properties.
[0049] Hereinafter, components (optical films and optical members) of the liquid crystal display device will be described.
[0050] B. LCD panel
[0051] B-1. Liquid crystal unit
[0052] The liquid crystal cell 10 has a pair of substrates 11, 12 and a liquid crystal layer 13 as a display medium sandwiched between the substrates. In terms of a conventional structure, a color filter and a black matrix are provided on one substrate 11, and a switching device for controlling the electro-optical characteristics of the liquid crystal, a scanning line for providing a gate signal to the switching device, a signal line for providing a source signal, a pixel electrode, and a counter electrode are provided on the other substrate 12. The interval (cell gap) between the above-mentioned substrates 11 and 12 can be controlled by a spacer or the like. An alignment film, for example, formed of polyimide, can be provided on the side of the above-mentioned substrates 11 and 12 in contact with the liquid crystal layer 13.
[0053] In one embodiment, the liquid crystal layer 13 includes liquid crystal molecules oriented in a homogeneous alignment in the absence of an electric field. Typically, the refractive index ellipsoid of such a liquid crystal layer (resulting in a liquid crystal unit) shows a relationship of nx>ny=nz. Representative examples of driving modes using such a liquid crystal layer showing a three-dimensional refractive index include an in-plane switching (IPS) mode and a fringe field switching (FFS) mode. The IPS mode includes a Super In-Plane Switching (S-IPS) mode and an Advanced Super In-Plane Switching (AS-IPS) mode using V-shaped electrodes or sawtooth electrodes. The FFS mode includes an Advanced Fringe-Field Switching (A-FFS) mode and an Ultra Fringe-Field Switching (U-FFS) mode using V-shaped electrodes or sawtooth electrodes. In a driving mode (such as IPS mode and FFS mode) that uses liquid crystal molecules that are oriented along a surface in the absence of an electric field, there is no tilted grayscale inversion and the tilted viewing angle is wide, so there is an advantage of excellent visual confirmation when observing from an oblique direction.
[0054] In another embodiment, the liquid crystal layer 13 includes liquid crystal molecules oriented in a homeotropic alignment in the absence of an electric field. As a driving mode using liquid crystal molecules oriented in a homeotropic alignment in the absence of an electric field, for example, a vertical alignment (VA) mode can be cited. The VA mode includes a multi-domain VA (MVA) mode. In the case of a driving mode (such as a VA mode) using such liquid crystal molecules oriented in a homeotropic alignment in the absence of an electric field, since the transmittance of the halftone in the oblique direction is higher than the transmittance of the halftone in the front direction, there is an advantage that the halftone observed from the oblique direction is bright and less black.
[0055] B-2. Polarizer
[0056] Any appropriate polarizer may be used as the first polarizer 20 and the second polarizer 30. The materials, thicknesses, optical properties, etc. of the first polarizer 20 and the second polarizer 30 may be the same or different. Hereinafter, the first polarizer 20 and the second polarizer 30 may be collectively referred to as polarizers.
[0057] The resin film forming the polarizer may be a single-layer resin film or a laminate of two or more layers.
[0058] Specific examples of polarizers made of a single-layer resin film include those obtained by dyeing and stretching hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formalized PVA films, and partially saponified films of ethylene-vinyl acetate copolymers using dichroic substances such as iodine and dichroic dyes; polyene-based oriented films such as dehydrated PVA films and dehydrochlorinated polyvinyl chloride films, etc. In terms of excellent optical properties, it is preferred to use a polarizer obtained by dyeing a PVA film with iodine and uniaxially stretching it.
[0059] The dyeing using iodine can be performed, for example, by immersing the PVA film in an iodine aqueous solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching can be performed after the dyeing treatment, or it can be performed while dyeing. In addition, it can also be dyed after stretching. The PVA film can be subjected to swelling treatment, cross-linking treatment, cleaning treatment, drying treatment, etc. as needed. For example, before dyeing, the PVA film is immersed in water for washing, thereby not only cleaning the stains and anti-blocking agent on the surface of the PVA film, but also swelling the PVA film to prevent uneven dyeing.
[0060] As specific examples of polarizers obtained using laminates, there can be cited polarizers obtained using a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a laminate of a resin substrate and a PVA-based resin layer formed by coating the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating the resin substrate can be made, for example, in the following manner: a PVA-based resin solution is applied to a resin substrate, dried to form a PVA-based resin layer on the resin substrate, thereby obtaining a laminate of the resin substrate and the PVA-based resin layer; the laminate is stretched and dyed to make the PVA-based resin layer into a polarizer. With respect to the present embodiment, stretching typically includes immersing the laminate in an aqueous boric acid solution and stretching it. Furthermore, stretching may further include stretching the laminate in the air at a high temperature (e.g., above 95° C.) before stretching in an aqueous boric acid solution, as needed. The obtained laminate of resin substrate / polarizer can be used directly (that is, the resin substrate can be used as a protective layer of polarizer), or the resin substrate can be peeled off from the laminate of resin substrate / polarizer, and any appropriate protective layer corresponding to the purpose can be stacked on the peeling surface for use. The details of the manufacturing method of such a polarizer are, for example, recorded in Japanese Patent Publication No. 2012-73580. The overall description of the publication is cited in this specification as a reference.
[0061] The thickness of the polarizer is preferably 15 μm or less, more preferably 1 μm to 12 μm, further preferably 3 μm to 10 μm, and particularly preferably 3 μm to 8 μm. When the thickness of the polarizer is in this range, curling during heating can be well suppressed and good appearance durability during heating can be obtained. Furthermore, when the thickness of the polarizer is in this range, it can contribute to the thinning of the liquid crystal display device.
[0062] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is preferably 43.0% to 46.0%, more preferably 44.5% to 46.0%. The polarization degree of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and further preferably 99.9% or more.
[0063] As described above, a protective film may be disposed on one side or both sides of the first polarizer 20, and a protective film may be disposed on one side or both sides of the second polarizer 30. That is, the polarizer may be used alone as a component of the liquid crystal display device, or in the form of a polarizing plate including the polarizer and the protective film as a component of the liquid crystal display device. Furthermore, the polarizer and the protective film may be laminated separately (i.e., the polarizer and the protective film are separated) as a component of the liquid crystal display device.
[0064] The protective film is formed by any appropriate film. As the specific example of the material that becomes the main component of this film, cellulose resins such as triacetyl cellulose (TAC), polyester, polyvinyl alcohol, polycarbonate, polyamide, polyimide, polyether sulfone, polysulfone, polystyrene, polynorbornene, polyolefin, (meth) acrylic acid, transparent resins such as acetate, etc. can be listed. In addition, thermosetting resins or ultraviolet curing resins such as (meth) acrylic acid, carbamate, (meth) acrylic acid carbamate, epoxy, silicone, etc. can also be listed. In addition, for example, glassy polymers such as siloxane polymers can also be listed. In addition, the polymer film recorded in Japanese Patent Publication No. 2001-343529 (WO01 / 37007) can also be used. As the material of the film, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain can be used, for example, a resin composition containing an alternating copolymer formed of isobutylene and N-methylmaleimide and an acrylonitrile-styrene copolymer can be cited. The polymer film can be, for example, an extrusion molding of the above resin composition.
[0065] The thickness of the protective film is preferably 20 μm to 200 μm, more preferably 30 μm to 100 μm, and even more preferably 35 μm to 95 μm.
[0066] When a protective film (inner protective film) is disposed on the liquid crystal cell 10 side of the first polarizer 20 and / or the second polarizer 30, the inner protective film is preferably optically isotropic. In this specification, "optically isotropic" means that the in-plane phase difference Re (550) is 0 nm to 10 nm and the phase difference Rth (550) in the thickness direction is -10 nm to +10 nm.
[0067] C. First phase difference layer
[0068] As described above, the in-plane phase difference Re (550) of the first phase difference layer 200 is 100nm to 180nm, preferably 110nm to 170nm, further preferably 120nm to 160nm, and particularly preferably 135nm to 155nm. That is, the first phase difference layer can function as a so-called λ / 4 plate. Therefore, the first phase difference layer has the function of converting the linear polarized light emitted by the polarizer to the visual confirmation side into elliptically polarized light or circularly polarized light. In this way, by configuring the first phase difference layer that can function as a λ / 4 plate to be closer to the visual confirmation side than the visual confirmation side polarizer (first polarizer 20) in the specific axial relationship as described above, even when the display screen is visually confirmed through an optical component with a polarization effect (such as polarized sunglasses), excellent visual confirmation can be achieved. Therefore, the liquid crystal display device of the present invention can be suitable for outdoor use.
[0069] Furthermore, as described above, the first phase difference layer satisfies the relationship of Re(450)<Re(550)<Re(650). That is, the first phase difference layer shows wavelength dependence of reverse dispersion in which the phase difference value increases with the wavelength of the measurement light. Re(450) / Re(550) of the first phase difference layer is preferably greater than 0.8 and less than 1.0, and more preferably 0.8 to 0.95. Re(550) / Re(650) is preferably greater than 0.8 and less than 1.0, and more preferably 0.8 to 0.97.
[0070] Typically, the refractive index characteristics of the first phase difference layer show a relationship of nx>ny, and have a slow axis. As described above, the angle between the slow axis of the first phase difference layer 200 and the absorption axis of the first polarizer 20 is preferably 35° to 55°, more preferably 38° to 52°, further preferably 40° to 50°, particularly preferably 42° to 48°, particularly preferably 44° to 46°, and most preferably about 45°. When the angle is in this range, by setting the first phase difference layer to a λ / 4 plate and arranging the first phase difference layer to be closer to the visual confirmation side than the first polarizer (visual confirmation side polarizer), excellent visual confirmation can be achieved even when the display screen is visually confirmed through an optical component with a polarization effect (such as polarized sunglasses). Therefore, the liquid crystal display device of the present invention can also be suitable for outdoor use.
[0071] As long as the first phase difference layer has the relationship nx>ny, it will show any appropriate refractive index ellipsoid. Preferably, the refractive index ellipsoid of the first phase difference layer shows the relationship nx>nz>ny. The Nz coefficient of the first phase difference layer is preferably 0.2-0.8, more preferably 0.3-0.7, further preferably 0.4-0.6, and particularly preferably about 0.5. By satisfying this relationship, there is an advantage of suppressing coloration when observing from an oblique direction through an optical component with a polarizing effect (such as polarized sunglasses).
[0072] The absolute value of the photoelastic coefficient of the first retardation layer is preferably 2×10 -11 m 2 / N or less, more preferably 2.0×10 -13 m 2 / N~1.5×10 -11 m 2 / N, more preferably 1.0×10 -12 m 2 / N~1.2×10 -11 m 2 When the absolute value of the photoelastic coefficient is within this range, the phase difference is unlikely to change when shrinkage stress is generated during heating. As a result, thermal unevenness in the liquid crystal display device can be well prevented.
[0073] The thickness of the first phase difference layer can be set in a manner that the λ / 4 plate can function most appropriately. In other words, the thickness can be set in a manner that a desired in-plane phase difference is obtained. Specifically, the thickness is preferably 1 μm to 80 μm, more preferably 10 μm to 80 μm, further preferably 10 μm to 60 μm, and particularly preferably 30 μm to 50 μm.
[0074] The first phase difference layer is formed of any appropriate resin that can satisfy the above characteristics. Examples of the resin forming the first phase difference layer include polycarbonate resin, polyvinyl acetal resin, cycloolefin resin, acrylic resin, cellulose ester resin, etc. Polycarbonate resin is preferred.
[0075] As the above-mentioned polycarbonate resin, any appropriate polycarbonate resin can be used as long as the effect of the present invention can be obtained. Preferably, the polycarbonate resin comprises a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from at least one dihydroxy compound selected from the group consisting of alicyclic diols, alicyclic dimethanol, diethylene glycol, triethylene glycol or polyethylene glycol and an alkylene glycol or spiro glycol. Preferably, the polycarbonate resin comprises a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, a structural unit derived from alicyclic dimethanol and / or a structural unit derived from diethylene glycol, triethylene glycol or polyethylene glycol, and further preferably comprises a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from diethylene glycol, triethylene glycol or polyethylene glycol. The polycarbonate resin may also optionally contain other structural units derived from dihydroxy compounds. In addition, the details of the polycarbonate resin that can be suitably used in the present invention are described in, for example, Japanese Patent Application Laid-Open Nos. 2014-10291 and 2014-26266, and the contents of these descriptions are incorporated herein by reference.
[0076] The glass transition temperature of the polycarbonate resin is preferably 110°C to 250°C, more preferably 120°C to 230°C. When the glass transition temperature is too low, there is a tendency for heat resistance to deteriorate, which may cause dimensional changes after film molding, or there is a case where the image quality of the resulting liquid crystal display device is reduced. When the glass transition temperature is too high, there is a case where the molding stability during film molding deteriorates, or there is a case where the transparency of the film is impaired. In addition, the glass transition temperature is obtained in accordance with JIS K 7121 (1987).
[0077] The molecular weight of the above-mentioned polycarbonate resin can be expressed by a reduced viscosity. The reduced viscosity is measured by using dichloromethane as a solvent, accurately adjusting the polycarbonate concentration to 0.6 g / dL, and using an Ubbelohde viscometer at a temperature of 20.0°C ± 0.1°C. The lower limit of the reduced viscosity is usually preferably 0.30 dL / g, and more preferably 0.35 dL / g or more. The upper limit of the reduced viscosity is usually preferably 1.20 dL / g, more preferably 1.00 dL / g, and further preferably 0.80 dL / g. When the reduced viscosity is less than the above lower limit, there is a situation where the mechanical strength of the molded product is reduced. On the other hand, when the reduced viscosity is greater than the above upper limit, there is a situation where the fluidity during molding is reduced, and the productivity or moldability is reduced.
[0078] The phase difference film constituting the first phase difference layer can be obtained, for example, by stretching a film formed by the above-mentioned polycarbonate resin. As a method for forming a film from a polycarbonate resin, any appropriate molding method can be used. As specific examples, there can be cited: compression molding, transfer molding, injection molding, extrusion molding, blow molding, powder molding, FRP (Fiber Reinforced Plastics; fiber reinforced plastic) molding, casting coating (such as casting), calendering, hot pressing, etc. Extrusion molding or casting coating is preferred. The reason is that the smoothness of the obtained film can be improved to obtain good optical uniformity. The molding conditions can be appropriately set according to the composition or type of the resin used, the desired properties of the phase difference film, etc.
[0079] The thickness of the resin film (unstretched film) can be set to any appropriate value depending on the desired thickness of the obtained retardation film, desired optical properties, stretching conditions described below, etc. It is preferably 50 μm to 300 μm.
[0080] The stretching may be performed by any appropriate stretching method and stretching conditions (e.g., stretching temperature, stretching ratio, stretching direction). Specifically, various stretching methods such as free end stretching, fixed end stretching, free end shrinking, fixed end shrinking, etc. may be used alone, simultaneously or successively. In terms of the stretching direction, the stretching may be performed in various directions or dimensions such as the length direction, width direction, thickness direction, and oblique direction.
[0081] By appropriately selecting the stretching method and stretching conditions, a retardation film having the desired optical properties (eg, refractive index properties, in-plane retardation, Nz coefficient) can be obtained.
[0082] In one embodiment, the phase difference film is produced by uniaxially stretching or fixed-end uniaxially stretching a resin film. As a specific example of fixed-end uniaxial stretching, a method of stretching the resin film in the width direction (transverse direction) while moving the resin film in the length direction can be cited. The stretching ratio is preferably 1.1 to 3.5 times.
[0083] In another embodiment, the phase difference film can be made by continuously tilting and stretching a long strip of resin film in the direction of a specified angle relative to the length direction. By adopting tilted stretching, a long strip of stretched film having an orientation angle of a specified angle relative to the length direction of the film (having a slow axis in the direction of a specified angle) can be obtained, for example, when stacked with a polarizer, it can be roll-to-roll, thereby simplifying the manufacturing steps. In addition, the above-mentioned specified angle can be the angle between the absorption axis of the first polarizer and the slow axis of the first phase difference layer in the liquid crystal display device. As described above, the angle is preferably 35° to 55°, more preferably 38° to 52°, further preferably 40° to 50°, particularly preferably 42° to 48°, particularly preferably 44° to 46°, and most preferably about 45°.
[0084] As a stretching machine used for oblique stretching, for example, a tenter-type stretching machine that can impart a conveying force or a stretching force or a drawing force at different speeds in the horizontal and / or vertical directions can be cited. The tenter-type stretching machine includes a horizontal uniaxial stretching machine, a synchronous biaxial stretching machine, etc. Any appropriate stretching machine can be used as long as the long strip resin film can be continuously obliquely stretched.
[0085] By appropriately controlling the left and right speeds of the stretching machine, a retardation film (substantially a long retardation film) having the desired in-plane retardation and a slow axis in the desired direction can be obtained.
[0086] Examples of the oblique stretching method include methods described in Japanese Patent Application Laid-Open Nos. 50-83482, 2-113920, 3-182701, 2000-9912, 2002-86554, and 2002-22944.
[0087] The retardation film suitable for the embodiment of the present invention (i.e., the retardation film having an Nz coefficient of less than 1.0) can be prepared by laminating a heat shrinkable film to one or both sides of a resin film via, for example, an acrylic adhesive to form a laminate, and subjecting the laminate to the stretching as described above. By adjusting the composition (e.g., shrinkage force) and stretching conditions (e.g., stretching temperature) of the heat shrinkable film, a retardation film having a desired Nz coefficient can be obtained.
[0088] The stretching temperature of the above-mentioned film can vary according to the desired in-plane phase difference value and thickness of the phase difference film, the type of resin used, the thickness of the film used, the stretching ratio, etc. Specifically, the stretching temperature is preferably Tg-30°C to Tg+30°C, more preferably Tg-15°C to Tg+15°C, and most preferably Tg-10°C to Tg+10°C. By stretching at this temperature, a phase difference film with appropriate characteristics can be obtained in the present invention. In addition, Tg is the glass transition temperature of the constituent material of the film.
[0089] Commercially available films may also be used as polycarbonate resin films. Specific examples of commercial products include "PURE-ACE WR-S", "PURE-ACE WR-W", and "PURE-ACE WR-M" manufactured by Teijin Co., Ltd., and "NRF" manufactured by Nitto Denko Co., Ltd. The commercially available film may be used as it is, or may be subjected to secondary processing (e.g., stretching treatment, surface treatment) according to the purpose.
[0090] D. Backlight source
[0091] The backlight source 300 is included in a backlight unit (not shown). In addition to the light source, the backlight unit typically also includes a light guide plate, a diffuser, a prism, etc. As described above, the backlight source has a discontinuous emission spectrum. "Having a discontinuous emission spectrum" means that there are clear peaks in each wavelength region of red (R), green (G) and blue (B) and the peaks are clearly distinguished. Figure 2 is a diagram schematically showing an example of a discontinuous emission spectrum. Figure 2 As shown, the emission spectrum of the backlight light source has a peak P1 in a wavelength region preferably between 430nm and 470nm, more preferably between 440nm and 460nm (blue wavelength region), a peak P2 in a wavelength region preferably between 530nm and 570nm, more preferably between 540nm and 560nm (green wavelength region), and a peak P3 in a wavelength region preferably between 630nm and 670nm, more preferably between 640nm and 660nm (red wavelength region). Preferably, the wavelength λ1, height hP1 and half-peak width Δλ1 of the peak P1, the wavelength λ2, height hP2 and half-peak width Δλ2 of the peak P2, the wavelength λ3, height hP3 and half-peak width Δλ3 of the peak P3, the height hB1 of the valley between the peak P1 and the peak P2, and the height hB2 of the valley between the peak P2 and the peak P3 satisfy the following relations (1) to (3):
[0092] (λ2-λ1) / (Δλ2+Δλ1)>1 (1)
[0093] (λ3-λ2) / (Δλ3+Δλ2)>1 (2)
[0094] 0.8≤{hP2-(hB2+hB1) / 2} / hP2≤1 (3).
[0095] (λ2-λ1) / (Δλ2+Δλ1) in formula (1) is more preferably 1.01 to 2.00, and further preferably 1.10 to 1.50. (λ3-λ2) / (Δλ3+Δλ2) in formula (2) is more preferably 1.01 to 2.00, and further preferably 1.10 to 1.50. {hP2-(hB2+hB1) / 2} in formula (3) is more preferably 0.85 to 1, and further preferably 0.9 to 1. Formula (1) means that the relationship between blue light and green light is that they are independent as light sources without mixing. Formula (2) means that the relationship between green light and red light is that they are independent as light sources without mixing. Formula (3) means that the valley between peaks P1, P2 and P3 is low and the peaks of blue light, green light and red light are clearly distinguished. By specifying formulas (1) to (3), there is an advantage of improved color reproducibility. By the synergistic effect of the backlight source 300 having an emission spectrum satisfying equations (1) to (3) and the first phase difference layer 200, a liquid crystal display device having excellent color reproducibility, excellent visual confirmation when visually confirmed through an optical member having a polarizing effect, and suppressed color unevenness can be realized. Figure 3 Compared with the existing backlight source with the emission spectrum shown (a white light source composed of a combination of LEDs emitting only red, green and blue light), color reproducibility, visibility when visually confirmed through an optical component with a polarizing effect, and color unevenness can all be significantly improved.
[0096] The backlight source may be any suitable configuration that can achieve the above-mentioned emission spectrum. In one embodiment, the backlight source includes an LED that emits red light, an LED that emits green light, and an LED that emits blue light, and the phosphor of the LED that emits red light is activated by tetravalent manganese ions. By activating the phosphor of the LED that emits red light, the backlight source may be reduced. Figure 3 The red and green light in the emission spectrum shown overlap, which can achieve Figure 2 Preferred specific examples of such red phosphors activated by tetravalent manganese ions include Mn ions listed in “INORGANIC PHOSPHORS” by William M. Yen and Marvin J. Weber, CRC, p. 212 (SECTION 4: 4.10 Miscellaneous Oxides of PHOSPHOR DATA). 4+ Activate Mg fluorogermanate phosphor (2.5MgO·MgF 2 :Mn 4+) and Journal of the Electrochemical Society: SOLID-STATE SCIENCE AND TECHNOLOGY, July 1973, p. 942. 1 2 M 2 F 6 :Mn 4+ (M 1 =Li, Na, K, Rb, Cs; M 2 =Si, Ge, Sn, Ti, Zr) phosphor. A backlight source using such a red phosphor is described in, for example, Japanese Patent Publication No. 2015-52648. In addition, a backlight source of a conventional structure including a red LED, a green LED, and a blue LED is described in, for example, Japanese Patent Publication No. 2012-256014. The contents of these publications are incorporated herein by reference.
[0097] In another embodiment, the backlight source includes an LED that emits blue light and a wavelength conversion layer that includes quantum dots. In this configuration, part of the blue light emitted by the LED is converted into red light and green light through the wavelength conversion layer, and part of the blue light is directly emitted as blue light. As a result, white light can be achieved. Furthermore, by appropriately configuring the wavelength conversion layer, an emission spectrum ( Figure 2 emission spectrum as shown).
[0098] Typically, the wavelength conversion layer comprises a matrix and quantum dots dispersed in the matrix. As a material constituting the matrix (hereinafter also referred to as a matrix material), any appropriate material can be used. As such a material, resins, organic oxides, and inorganic oxides can be cited. The matrix material preferably has low oxygen permeability and moisture permeability, high light stability and chemical stability, a specified refractive index, excellent transparency, and / or excellent dispersibility for quantum dots. When these are considered comprehensively, the matrix material is preferably a resin. The resin may be a thermoplastic resin, a thermosetting resin, or an active energy ray-curable resin (e.g., an electron beam-curable resin, an ultraviolet-curable resin, or a visible light-curable resin). Preferably, it is a thermosetting resin or an ultraviolet-curable resin, and more preferably a thermosetting resin. The resin may be used alone or in combination (e.g., blended, copolymerized).
[0099] Quantum dots can control the wavelength conversion characteristics of the wavelength conversion layer. Specifically, by appropriately combining quantum dots with different luminescent center wavelengths, a wavelength conversion layer that realizes light with a desired luminescent center wavelength can be formed. The luminescent center wavelength of quantum dots can be adjusted by the material and / or composition, particle size, shape, etc. of the quantum dots. As quantum dots, for example, quantum dots with a luminescent center wavelength in the band of 600nm to 680nm (hereinafter referred to as quantum dots A), quantum dots with a luminescent center wavelength in the band of 500nm to 600nm (hereinafter referred to as quantum dots B), and quantum dots with a luminescent center wavelength in the band of 400nm to 500nm (hereinafter referred to as quantum dots C) are known. Quantum dot A is excited by excitation light (light from the backlight source in the present invention) and emits red light, quantum dot B emits green light, and quantum dot C emits blue light. By appropriately combining them, light of a specified wavelength (light from the backlight source) is incident and passes through the wavelength conversion layer, and light with a luminescent center wavelength in the desired band can be realized.
[0100] The quantum dots may be made of any suitable material. The quantum dots may preferably be made of an inorganic material, more preferably an inorganic conductor material or an inorganic semiconductor material. As semiconductor materials, for example, semiconductors of Group II-VI, Group III-V, Group IV-VI, and Group IV may be cited. Specific examples include Si, Ge, Sn, Se, Te, B, C (including diamond), P, BN, BP, BAs, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, InSb, ZnO, ZnS, ZnSe, ZnTe, CdS, CdSe, CdSeZn, CdTe, HgS, HgSe, HgTe, BeS, BeSe, BeTe, MgS, MgSe, GeS, GeSe, GeTe, SnS, SnSe, SnTe, PbO, PbS, PbSe, PbTe, CuF, CuCl, CuBr, CuI, Si 3 N 4 ,Ge 3 N 4 、Al 2 O 3 、(Al、Ga、In) 2 (S, Se, Te) 3 、Al 2 CO. These may be used alone or in combination of two or more. The quantum dot may contain a p-type dopant or an n-type dopant.
[0101] The size of the quantum dot can be any appropriate size according to the desired emission wavelength. The size of the quantum dot is preferably 1nm to 10nm, more preferably 2nm to 8nm. When the size of the quantum dot is in this range, green and red respectively show distinct luminescence, thereby achieving high color rendering. For example, green light can emit light when the size of the quantum dot is about 7nm, and red light can emit light at about 3nm. As for the size of the quantum dot, when the quantum dot is, for example, a true spherical shape, it is the average particle size, and when it is a shape other than this, it is the size along the smallest axis in the shape. In addition, as the shape of the quantum dot, any appropriate shape can be adopted according to the purpose. As specific examples, true spherical, scaly, plate-like, ellipsoidal, and irregular shapes can be listed.
[0102] The quantum dots are preferably blended in an amount of 1 to 50 parts by weight, more preferably 2 to 30 parts by weight, relative to 100 parts by weight of the matrix material. When the blending amount of the quantum dots is within this range, a liquid crystal display device having excellent RGB color balance can be realized.
[0103] The details of quantum dots are described in, for example, Japanese Patent Application Laid-Open No. 2012-169271, Japanese Patent Application Laid-Open No. 2015-102857, Japanese Patent Application Laid-Open No. 2015-65158, Japanese Patent Application No. 2013-544018, Japanese Patent Application No. 2013-544018, and Japanese Patent Application No. 2010-533976, and the contents of these publications are incorporated herein by reference. Commercially available quantum dots may also be used.
[0104] The thickness of the wavelength conversion layer is preferably 1 μm to 500 μm, and more preferably 100 μm to 400 μm. When the thickness of the wavelength conversion layer is within such a range, excellent conversion efficiency and durability can be achieved.
[0105] The wavelength conversion layer is arranged in the form of a thin film on the emission side of the LED (light source) in the backlight unit.
[0106] E. Second phase difference layer
[0107] As described above, the refractive index characteristics of the second phase difference layer 400 show the relationship of nz>nx≥ny. The phase difference Rth(550) in the thickness direction of the second phase difference layer is preferably -260nm~-10nm, more preferably -230nm~-15nm, and further preferably -215nm~-20nm. By providing a second phase difference layer having such optical characteristics, the coloring when observed from an oblique direction through an optical component having a polarizing effect (such as polarized sunglasses) is significantly improved, resulting in a liquid crystal display device with very excellent viewing angle characteristics.
[0108] In one embodiment, the refractive index of the second phase difference layer shows a relationship of nx=ny. In another embodiment, the refractive index of the second phase difference layer shows a relationship of nx>ny. Therefore, there is a case where the second phase difference layer has a slow axis. In this case, the slow axis of the second phase difference layer is substantially orthogonal or parallel to the absorption axis of the first polarizer 20. In addition, the in-plane phase difference Re(550) of the second phase difference layer is preferably 10nm to 150nm, and more preferably 10nm to 80nm.
[0109] The second phase difference layer can be formed by any appropriate material. It is preferably a liquid crystal layer fixed in a vertical orientation. The liquid crystal material (liquid crystal compound) that can be vertically oriented can be either a liquid crystal monomer or a liquid crystal polymer. As specific examples of the liquid crystal compound and the method for forming the liquid crystal layer, the liquid crystal compound and the method for forming the liquid crystal layer described in
[0020] to
[0042] of Japanese Patent Gazette No. 2002-333642 can be cited. In this case, the thickness is preferably 0.1 μm to 5 μm, and more preferably 0.2 μm to 3 μm.
[0110] As another preferred specific example, the second retardation layer may be a retardation film formed of a fumaric acid diester resin described in Japanese Patent Application Laid-Open No. 2012-32784. In this case, the thickness is preferably 5 to 80 μm, more preferably 10 to 50 μm.
[0111] F. Conductive layer
[0112] Typically, the conductive layer (not shown) is transparent (ie, the conductive layer is a transparent conductive layer). By forming a conductive layer between the first polarizer 20 and the liquid crystal cell 10, the liquid crystal display device can function as a so-called built-in touch panel type input display device.
[0113] The conductive layer can be used alone as a constituent layer of a liquid crystal display device, or can be provided to the liquid crystal display device in the form of a laminate with a substrate (conductive layer with a substrate). In the case of being constituted by a conductive layer alone, the conductive layer can be transferred from the substrate on which the conductive layer is formed to a predetermined position of the liquid crystal display device.
[0114] The conductive layer can be patterned as needed. By patterning, a conductive portion and an insulating portion can be formed. As a result, an electrode can be formed. The electrode can function as a touch sensor electrode that senses contact with a touch panel. The shape of the pattern is preferably a pattern that works well as a touch panel (e.g., an electrostatic capacitance touch panel). As specific examples, patterns described in Japanese Patent Publication No. 2011-511357, Japanese Patent Publication No. 2010-164938, Japanese Patent Publication No. 2008-310550, Japanese Patent Publication No. 2003-511799, and Japanese Patent Publication No. 2010-541109 can be cited.
[0115] The total light transmittance of the conductive layer is preferably 80% or more, more preferably 85% or more, and further preferably 90% or more. For example, when the following conductive nanowires are used, a transparent conductive layer having openings can be formed, thereby obtaining a transparent conductive layer with high light transmittance.
[0116] The density of the conductive layer is preferably 1.0 g / cm 3 ~10.5g / cm 3 , more preferably 1.3 g / cm 3 ~3.0g / cm 3 .
[0117] The surface resistance value of the conductive layer is preferably 0.1 Ω / sq to 1000 Ω / sq, more preferably 0.5 Ω / sq to 500 Ω / sq, and further preferably 1 Ω / sq to 250 Ω / sq.
[0118] Representative examples of the conductive layer include a conductive layer comprising a metal oxide, a conductive layer comprising conductive nanowires, and a conductive layer comprising a metal mesh. A conductive layer comprising conductive nanowires or a conductive layer comprising a metal mesh is preferred. The reason for this is that the conductive layer has excellent bending resistance and the conductivity is not easily lost even when bent, so a conductive layer that can be bent well can be formed. As a result, the liquid crystal display device can be configured to be bendable.
[0119] The conductive layer containing the metal oxide can be formed by forming a metal oxide film on any appropriate substrate by any appropriate film forming method (e.g., vacuum evaporation, sputtering, CVD (Chemical Vapor Deposition), ion plating, spraying, etc.). As the metal oxide, for example, indium oxide, tin oxide, zinc oxide, indium-tin composite oxide, tin-antimony composite oxide, zinc-aluminum composite oxide, indium-zinc composite oxide can be listed. Among them, indium-tin composite oxide (ITO) is preferred.
[0120] The conductive layer containing conductive nanowires can be formed by applying a dispersion (conductive nanowire dispersion) obtained by dispersing conductive nanowires in a solvent on any appropriate substrate and then drying the coating layer. As conductive nanowires, any appropriate conductive nanowires can be used as long as the effect of the present invention can be obtained. Conductive nanowires refer to conductive substances with a needle-like or wire-like shape and a nanometer diameter. Conductive nanowires can be either straight or curved. As described above, the conductive layer containing conductive nanowires has excellent bending resistance. In addition, the conductive layer containing conductive nanowires is formed into a grid shape by forming gaps between the conductive nanowires, so that even a small amount of conductive nanowires can form a good conductive path, thereby obtaining a conductive layer with low resistance. Furthermore, by making the conductive nanowires into a grid shape, an opening can be formed in the gap of the grid to obtain a conductive layer with high light transmittance. As conductive nanowires, for example, metal nanowires composed of metals, conductive nanowires containing carbon nanotubes, etc. can be listed.
[0121] The ratio of the thickness d of the conductive nanowire to the length L (aspect ratio: L / d) is preferably 10 to 100,000, more preferably 50 to 100,000, and further preferably 100 to 10,000. When using conductive nanowires with such a large aspect ratio, the conductive nanowires are well crossed and can exhibit a higher conductivity than a small amount of conductive nanowires. As a result, a conductive layer with high light transmittance can be obtained. In addition, in this specification, "the thickness of the conductive nanowire" refers to its diameter when the cross-section of the conductive nanowire is circular, refers to its short diameter when it is elliptical, and refers to the longest diagonal when it is polygonal. The thickness and length of the conductive nanowire can be confirmed by a scanning electron microscope or a transmission electron microscope.
[0122] The thickness of the conductive nanowire is preferably less than 500 nm, more preferably less than 200 nm, further preferably 1 nm to 100 nm, and particularly preferably 1 nm to 50 nm. When it is in this range, a conductive layer with high light transmittance can be formed. The length of the conductive nanowire is preferably 2.5 μm to 1000 μm, more preferably 10 μm to 500 μm, and further preferably 20 μm to 100 μm. When it is in this range, a conductive layer with high conductivity can be obtained.
[0123] As the metal constituting the conductive nanowire (metal nanowire), any appropriate metal can be used as long as it is a metal with high conductivity. The metal nanowire is preferably composed of one or more metals selected from gold, platinum, silver and copper. Among them, from the viewpoint of conductivity, silver, copper or gold is preferred, and silver is more preferred. In addition, materials that have been plated (e.g., gold-plated) with the above metals can also be used.
[0124] As the carbon nanotubes, any appropriate carbon nanotubes can be used. For example, so-called multi-layer carbon nanotubes, double-layer carbon nanotubes, single-layer carbon nanotubes, etc. can be used. Among them, single-layer carbon nanotubes are preferably used because of their high electrical conductivity.
[0125] As the metal mesh, any appropriate metal mesh may be used as long as the effects of the present invention can be obtained. For example, a metal mesh in which a metal wiring layer provided on a film substrate is patterned in a mesh shape may be used.
[0126] The details of the conductive nanowires and the metal mesh are described in, for example, Japanese Patent Application Laid-Open Nos. 2014-113705 and 2014-219667, the contents of which are incorporated herein by reference.
[0127] The thickness of the conductive layer is preferably 0.01 μm to 10 μm, more preferably 0.05 μm to 3 μm, and further preferably 0.1 μm to 1 μm. When it is in this range, a conductive layer with excellent conductivity and light transmittance can be obtained. In addition, when the conductive layer contains a metal oxide, the thickness of the conductive layer is preferably 0.01 μm to 0.05 μm.
[0128] G. Adhesive layer or adhesive layer
[0129] For lamination of each layer constituting the liquid crystal display device of the present invention and the optical member, any appropriate adhesive layer or adhesive layer can be used. Typically, the adhesive layer is formed of an acrylic adhesive. Typically, the adhesive layer is formed of a polyvinyl alcohol adhesive.
[0130] Example
[0131] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples. In addition, the measuring methods of each characteristic are as follows. In addition, unless otherwise specifically stated, the "parts" and "%" in the examples are weight references.
[0132] (1) Thickness
[0133] The measurement was performed using a dial gauge (manufactured by PEACOCK, product name "DG-205" and a dial gauge stand (product name "pds-2")).
[0134] (2) Phase difference
[0135] A sample of 50 mm×50 mm was cut out from each retardation film and liquid crystal cured layer as a measurement sample, and was measured using Axoscan manufactured by Axometrics Co., Ltd. The measurement wavelength was 450 nm and 550 nm, and the measurement temperature was 23°C.
[0136] In addition, the average refractive index was measured using an Abbe refractometer manufactured by Atomos Corporation, and the refractive indices nx, ny, and nz were calculated from the obtained phase difference values.
[0137] (3) Water absorption
[0138] The test is carried out in accordance with the "Test Method for Water Absorption and Boiling Water Absorption of Plastics" described in JIS K7209. The test piece is a square with a side length of 50 mm. The weight change before and after immersion in water at a temperature of 25°C is measured to obtain the value. The unit is %.
[0139] (4) Backlight spectrum measurement
[0140] The liquid crystal display device obtained in each embodiment and each comparative example was made to display a white image, and the emission spectrum was measured using SR-UL1R manufactured by Topcon. Figure 2 The wavelength λ1, wavelength λ2, wavelength λ3, height hP1, height hP2, height hP3, height hB1, height hB2, half-width Δλ1, half-width Δλ2 and half-width Δλ3 shown in the figure are used to obtain the following values shown by equations (4), (5) and (6). In addition, the spectrum of the display light when the liquid crystal display device displays a white image is made substantially equal to the emission spectrum of the backlight source, so the spectrum of the display light when the white image is displayed is set to the emission spectrum of the backlight source.
[0141] (λ2-λ1) / (Δλ2+Δλ1) (4)
[0142] (λ3-λ2) / (Δλ3+Δλ2) (5)
[0143] {hP2-(hB2+hB1) / 2} / hP2 (6)
[0144] (5) Visual confirmation evaluation
[0145] The liquid crystal display device obtained in each Example and each Comparative Example was made to display a white image, and the visibility when the image was observed through polarized sunglasses was evaluated based on the following criteria.
[0146] Good…no coloration or rainbow spots
[0147] Defective...coloring
[0148] <Example 1>
[0149] (Preparation of Phase Difference Film A Constituting the First Phase Difference Layer)
[0150] The polymerization was carried out using a batch polymerization apparatus comprising two vertical reactors equipped with stirring blades and a reflux condenser controlled at 100° C. 9,9-[4-(2-hydroxyethoxy)phenyl]fluorene (BHEPF), isosorbide (ISB), diethylene glycol (DEG), diphenyl carbonate (DPC) and magnesium acetate tetrahydrate were mixed in a molar ratio of BHEPF / ISB / DEG / DPC / magnesium acetate=0.348 / 0.490 / 0.162 / 1.005 / 1.00×10 -5 . After the reactor is fully substituted with nitrogen (oxygen concentration is 0.0005-0.00% by volume), it is heated by a heat medium and stirring is started when the internal temperature reaches 100°C. 40 minutes after the start of the temperature increase, the internal temperature is brought to 220°C and controlled in a manner to maintain the temperature. At the same time, the pressure is reduced and is set to 13.3 kPa 90 minutes after reaching 220°C. The phenol vapor produced as a by-product of the polymerization reaction is introduced into a reflux condenser at 100°C, and a certain amount of monomer components contained in the phenol vapor is returned to the reactor. The uncondensed phenol vapor is introduced into a condenser at 45°C and recovered.
[0151] After nitrogen is introduced into the first reactor and the pressure is temporarily restored to atmospheric pressure, the oligomerized reaction liquid in the first reactor is transferred to the second reactor. Next, the temperature and pressure reduction in the second reactor are started, and the internal temperature is set to 240°C and the pressure is set to 0.2 kPa in 50 minutes. Thereafter, polymerization is carried out until the specified stirring power is reached. When the specified power is reached, nitrogen is introduced into the reactor and the pressure is restored. The reaction liquid is taken out in the form of strands and pelletized using a rotary cutter to obtain a polycarbonate resin with a copolymer composition of BHEPF / ISB / DEG=34.8 / 49.0 / 16.2 [mol %]. The reduced viscosity of the polycarbonate resin is 0.430 dL / g and the glass transition temperature is 128°C. After the obtained polycarbonate resin was vacuum dried at 80°C for 5 hours, a polycarbonate resin film with a thickness of 70 μm was prepared using a film-making device equipped with a single screw extruder (manufactured by Isuzu Chemical Machinery Co., Ltd., with a screw diameter of 25 mm and a barrel setting temperature of 220°C), a T-die (width of 900 mm, setting temperature of 220°C), a cooling roller (setting temperature of 125°C) and a winder. The water absorption of the obtained polycarbonate resin film was 1.2%. The obtained polycarbonate resin film was uniaxially stretched to 2.0 times at 133°C to obtain a phase difference film A (thickness of 50 μm). The obtained phase difference film A had a Re(550) of 140 nm, a Rth(550) of 140 nm, and a Re(450) / Re(550) of 0.89.
[0152] (Fabrication of Polarizer)
[0153] A-PET (amorphous-polyethylene terephthalate) film (manufactured by Mitsubishi Plastics Co., Ltd., trade name: NOVACLEAR SH046 200 μm) was prepared as a substrate, and the surface was subjected to corona treatment (58 W / m 2 / minute). On the other hand, PVA (polymerization degree of 4200, saponification degree of 99.2%) to which 1 wt% of acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name: GOHSEFIMER Z200 (polymerization degree of 1200, saponification degree of 99.0% or more, acetoacetyl modification degree of 4.6%)) was added was prepared, applied on a substrate in such a manner that the film thickness after drying became 12 μm, and dried by hot air drying at 60° C. for 10 minutes, thereby preparing a laminate having a PVA-based resin layer provided on a substrate.
[0154] Next, the laminate is first stretched to 2.0 times in the MD direction (machine direction; longitudinal direction) at 130°C in air to generate a stretched laminate. Next, the following process is performed: the PVA layer after the PVA molecules contained in the stretched laminate are oriented is insolubilized by immersing the stretched laminate in a boric acid insolubilizing aqueous solution at a liquid temperature of 30°C for 30 seconds. The boric acid aqueous solution used for insolubilization in this process contains 3 parts by weight of boric acid relative to 100 parts by weight of water. A colored laminate is generated by dyeing the stretched laminate that has undergone the insolubilization process. The colored laminate is formed by immersing the stretched laminate in a dyeing solution so that the PVA layer contained in the stretched laminate adsorbs iodine. The dyeing solution contains iodine and potassium iodide, the liquid temperature of the dyeing solution is set to 30°C, water is used as a solvent, the iodine concentration is set to be in the range of 0.08 to 0.25 weight%, and the potassium iodide concentration is set to be in the range of 0.56 to 1.75 weight%. The concentration ratio of iodine to potassium iodide was set to 1 to 7. As dyeing conditions, the iodine concentration and immersion time were set so that the single transmission of the PVA-based resin layer constituting the polarizer would be 40.9%.
[0155] Next, the following process is performed: the PVA molecules of the PVA layer adsorbed with iodine are cross-linked by immersing the colored laminate in a cross-linking boric acid aqueous solution at 30°C for 60 seconds. The cross-linking boric acid aqueous solution used in the cross-linking process sets the boric acid content to 3 parts by weight relative to 100 parts by weight of water, and sets the potassium iodide content to 3 parts by weight relative to 100 parts by weight of water. Furthermore, the following stretching is performed: the obtained colored laminate is stretched to 2.7 times in the same direction as the previous stretching in the air at a stretching temperature of 70°C, so that the final stretching ratio becomes 5.4 times, and an optical film laminate containing a test polarizer is obtained. The boric acid aqueous solution used in the stretching process sets the boric acid content to 4.0 parts by weight relative to 100 parts by weight of water, and sets the potassium iodide content to 5 parts by weight relative to 100 parts by weight of water. The obtained optical film laminate is taken out from the boric acid aqueous solution, and the boric acid attached to the surface of the PVA layer is cleaned with an aqueous solution containing 4 parts by weight of potassium iodide relative to 100 parts by weight of water. The washed optical film laminate was dried in a drying step using hot air at 60° C., thereby obtaining a polarizer having a thickness of 5 μm laminated on a PET film.
[0156] (Production of polarizing plate with phase difference layer)
[0157] For the polarizer prepared as above, the polarizer with a thickness of 5 μm laminated on the PET film was laminated on the surface opposite to the PET through a UV (Ultraviolet) curable adhesive in such a way that the angle between the slow axis and the absorption axis of the polarizer was substantially 45°. The PET film was then peeled off from the laminate to obtain a polarizer with a phase difference layer.
[0158] (Manufacturing of Liquid Crystal Display Device)
[0159] The liquid crystal panel is taken out from the liquid crystal display device of a smartphone (XperiaZ4 manufactured by SONY: the emission spectrum of the backlight source is discontinuous) having an IPS liquid crystal display device, the polarizer disposed on the visual confirmation side of the liquid crystal unit is removed, and the glass surface of the liquid crystal unit is cleaned. Next, the surface on the polarizer side of the polarizer with a phase difference plate is laminated on the surface of the visual confirmation side of the liquid crystal unit through an acrylic adhesive (thickness of 20 μm) in a manner that the absorption axis of the polarizer is orthogonal to the initial orientation direction of the liquid crystal unit (the angle formed by the slow axis of the first phase difference layer and the long side of the liquid crystal panel is 45°, and the angle formed by the absorption axis of the polarizer and the long side of the liquid crystal panel is 0°) to obtain a liquid crystal panel. The backlight unit of the above-mentioned smartphone is installed on the above-mentioned liquid crystal panel laminated with a polarizer with a phase difference plate as the liquid crystal display device of this embodiment. The liquid crystal display device is made to display a white image, and the visual confirmation through polarized sunglasses is evaluated in the white image state. The evaluation results are shown in Table 1.
[0160] <Example 2>
[0161] (Preparation of Phase Difference Film B Constituting the First Phase Difference Layer)
[0162] The polycarbonate resin (10 kg) obtained in the same manner as in Example 1 was dissolved in dichloromethane (73 kg) to prepare a birefringent layer forming material. Next, the birefringent layer forming material was directly coated on a shrinkable film (longitudinally uniaxially stretched polypropylene film, manufactured by Tokyo Ink Co., Ltd., trade name "Noblen"), and the coating was dried at a drying temperature of 30°C for 5 minutes and at 80°C for 5 minutes to form a shrinkable film / birefringent layer laminate. The obtained laminate was stretched at a stretching temperature of 155°C in the MD direction at a shrinkage ratio of 0.80 using a simultaneous biaxial stretching machine, and stretched to 1.3 times in the TD direction (Transverse Direction), thereby forming a phase difference film B on the shrinkable film. Next, the phase difference film B was peeled off from the shrinkable film.
[0163] The retardation film B (thickness: 60 μm) was obtained in the above manner. The obtained retardation film B had Re(550) of 140 nm, Rth(550) of 70 nm, and Re(450) / Re(550) of 0.89. The slow axis direction of the retardation film B was 90° relative to the longitudinal direction.
[0164] (Production of polarizing plate with phase difference layer and liquid crystal display device)
[0165] A polarizing plate with a phase difference layer was prepared in the same manner as in Example 1 except that the phase difference film B was used instead of the phase difference film A, and a liquid crystal display device was prepared in the same manner as in Example 1 except that the polarizing plate with a phase difference layer was used. The liquid crystal display device was made to display a white image, and the visual confirmation through polarized sunglasses was evaluated in the white image state. The evaluation results are shown in Table 1.
[0166] <Example 3>
[0167] (Preparation of Liquid Crystal Cured Layer Constituting Second Retardation Layer)
[0168] A liquid crystal coating liquid was prepared by dissolving 20 parts by weight of a side chain liquid crystal polymer represented by the following chemical formula (I) (the numbers 65 and 35 in the formula represent the molar % of the monomer unit, and for convenience of explanation, it is represented by a block polymer: the weight average molecular weight is 5000), 80 parts by weight of a polymerizable liquid crystal showing a nematic liquid crystal phase (manufactured by BASF: trade name Paliocolor LC242), and 5 parts by weight of a photopolymerization initiator (manufactured by Ciba Specialty Chemicals: trade name Irgacure 907) in 200 parts by weight of cyclopentanone. Next, the coating liquid was applied to a substrate film (norbornene-based resin film: manufactured by Zeon Co., Ltd., Japan, trade name "ZEONEX") by a rod coater, and then heated and dried at 80°C for 4 minutes to align the liquid crystal. The liquid crystal layer was irradiated with ultraviolet rays to cure the liquid crystal layer, thereby forming a liquid crystal cured layer (thickness: 1.10 μm) serving as a second phase difference layer on the substrate film. The liquid crystal cured layer had a Re(550) of 0 nm and an Rth(550) of -100 nm, showing a refractive index characteristic of nz>nx=ny.
[0169]
[0170] (Production of polarizing plate with phase difference layer)
[0171] For the laminate of the PET film and the polarizer obtained in the same manner as in Example 1, the liquid crystal cured layer is bonded to the surface on the opposite side to the PET film via a UV curing adhesive in such a manner that the peeling direction of the substrate film when the substrate film is removed is substantially parallel to the absorption axis of the polarizer. Furthermore, the substrate film is removed, and the phase difference film A prepared in the same manner as in Example 1 is bonded to the side of the liquid crystal cured layer opposite to the polarizer via a UV curing adhesive in such a manner that the angle between its slow axis and the absorption axis of the polarizer is substantially 45°. Furthermore, after the PET film is peeled off from the laminate, an acrylic protective film or a phase difference layer is bonded via a UV curing adhesive as needed to prepare a polarizing plate with a phase difference layer.
[0172] (Manufacturing of Liquid Crystal Display Device)
[0173] A liquid crystal display device was prepared in the same manner as in Example 1 except that the polarizing plate with a phase difference layer and a smartphone with a different backlight source were used. The liquid crystal display device was made to display a white image, and visual confirmation through polarized sunglasses was evaluated in the white image state. The evaluation results are shown in Table 1.
[0174] <Example 4>
[0175] (Preparation of Phase Difference Film C Constituting the First Phase Difference Layer)
[0176] After the polycarbonate resin obtained in the same manner as in Example 1 was vacuum dried at 80° C. for 5 hours, a polycarbonate resin film having a thickness of 130 μm was prepared using a film forming apparatus equipped with a single screw extruder (manufactured by Isuzu Chemical Machinery Co., Ltd., screw diameter of 25 mm, barrel setting temperature: 220° C.), a T die (width of 900 mm, setting temperature: 220° C.), a cooling roll (setting temperature: 125° C.) and a winder. The water absorption of the obtained polycarbonate resin film was 1.2%.
[0177] The polycarbonate resin film was obliquely stretched by the method according to Example 1 of JP-A-2014-194483 to obtain a retardation film C.
[0178] The specific production sequence of phase difference film C is as follows: a polycarbonate resin film (thickness of 130 μm, width of 765 mm) is preheated to 142 ° C in the preheating area of the stretching device. In the preheating area, the clamp spacing of the left and right clamps is 125 mm. Next, the film is placed in the first inclined stretching area C1, and the clamp spacing of the right clamp is increased from 125 mm to 177.5 mm in the first inclined stretching area C1. The clamp spacing change rate is 1.42. In the first inclined stretching area C1, the clamp spacing of the left clamp begins to be reduced, so that it is reduced from 125 mm to 90 mm in the first inclined stretching area C1. The clamp spacing change rate is 0.72. Furthermore, the film is placed in the second inclined stretching area C2, and the clamp spacing of the left clamp is increased at the same time, so that it is increased from 90 mm to 177.5 mm in the second inclined stretching area C2. On the other hand, the clamp spacing of the right clamp is maintained at 177.5 mm in the second inclined stretching area C2. In addition, the film was stretched 1.9 times in the width direction simultaneously with the above-mentioned inclined stretching. In addition, the above-mentioned inclined stretching was performed at 135°C. Then, MD shrinkage treatment was performed in the shrinkage area. Specifically, the clamp spacing of the left clamp and the right clamp was reduced from 177.5 mm to 165 mm. The shrinkage rate in the MD shrinkage treatment was 7.0%.
[0179] The retardation film C (thickness: 40 μm) was obtained in the above manner. The obtained retardation film C had Re(550) of 140 nm, Rth(550) of 168 nm, and Re(450) / Re(550) of 0.89. The slow axis direction of the retardation film C was 45° with respect to the longitudinal direction.
[0180] (Production of polarizing plate with phase difference layer and liquid crystal display device)
[0181] A polarizing plate with a phase difference layer was prepared in the same manner as in Example 1 except that the phase difference film C was used instead of the phase difference film A, and a liquid crystal display device was prepared in the same manner as in Example 1 except that the polarizing plate with a phase difference layer was used. The liquid crystal display device was made to display a white image, and the visual confirmation through polarized sunglasses was evaluated in the white image state. The evaluation results are shown in Table 1.
[0182] <Comparative Example 1>
[0183] (Preparation of Phase Difference Film D Constituting the First Phase Difference Layer)
[0184] A biaxially stretched polypropylene film (manufactured by Toray, trade name "Torayfan" (thickness 60 μm)) was bonded to both sides of a commercially available ARTON film (manufactured by JSR, thickness 70 μm) via an acrylic adhesive layer (thickness 15 μm). Thereafter, the film was stretched to 1.45 times in an air circulation constant temperature oven at 147°C while maintaining the longitudinal direction of the film using a roll stretching machine to obtain a retardation film D. The obtained retardation film D had a Re (550) of 140 nm, a Rth (550) of 70 nm, and a Re (450) / Re (550) of 1.00.
[0185] (Production of polarizing plate with phase difference layer and liquid crystal display device)
[0186] A polarizing plate with a phase difference layer was prepared in the same manner as in Example 1 except that the phase difference film D was used instead of the phase difference film A, and a liquid crystal display device was prepared in the same manner as in Example 1 except that the polarizing plate with a phase difference layer was used. The liquid crystal display device was made to display a white image, and the visual confirmation through polarized sunglasses was evaluated in the white image state. The evaluation results are shown in Table 1.
[0187] <Comparative Example 2>
[0188] (Preparation of Phase Difference Film E Constituting the First Phase Difference Layer)
[0189] A commercially available ARTON film (manufactured by JSR Corporation, with a thickness of 100 μm) was stretched to 1.8 times in an air circulation constant temperature oven at 147° C. while maintaining the film in its longitudinal direction using a roll stretcher to obtain a retardation film E. The obtained retardation film E had a Re(550) of 140 nm, a Rth(550) of 140 nm, and a Re(450) / Re(550) of 1.00.
[0190] (Production of polarizing plate with phase difference layer)
[0191] A polarizing plate with a retardation layer was produced in the same manner as in Example 1 except that the retardation film E was used.
[0192] (Manufacturing of Liquid Crystal Display Device)
[0193] Take out the liquid crystal panel from the liquid crystal display device of a smartphone (iphone5 manufactured by Apple: the emission spectrum of the backlight source is continuous) with an IPS liquid crystal display device, remove the polarizer disposed on the visual confirmation side of the liquid crystal unit, and clean the glass surface of the liquid crystal unit. Next, the surface of the polarizer side of the polarizer with a phase difference plate is laminated on the surface of the visual confirmation side of the liquid crystal unit through an acrylic adhesive (thickness of 20 μm) in a manner that the absorption axis of the polarizer is orthogonal to the initial orientation direction of the liquid crystal unit, thereby obtaining a liquid crystal panel. The liquid crystal panel laminated with the polarizer with a phase difference plate is installed on the above-mentioned smartphone as the liquid crystal display device of this embodiment. The liquid crystal display device is made to display a white image, and the visual confirmation through polarized sunglasses is evaluated in the white image state. The evaluation results are shown in Table 1.
[0194] <Comparative Example 3>
[0195] (Preparation of Phase Difference Film F Constituting First Phase Difference Layer)
[0196] A polycarbonate resin [number average molecular weight (Mn) = 33000, Mw / Mn = 1.78] containing repeating units of the following chemical formulas (II) and (III) with a weight average molecular weight (Mw) of 60000 and a weight ratio of (A) to (B) of 4:6 was obtained according to a conventional method using phosgene as a carbonate precursor, (A) 2,2-bis(4-hydroxyphenyl)propane and (B) 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane as aromatic dihydric phenol components. 70 parts by weight of the polycarbonate resin and 30 parts by weight of a styrene resin [number average molecular weight (Mn) = 716, Mw / Mn = 1.78] (HIMER SB75 manufactured by Sanyo Chemical) with a weight average molecular weight (Mw) of 1300 were added to 300 parts by weight of dichloromethane and stirred and mixed at room temperature for 4 hours to obtain a transparent solution. The solution was cast onto a glass plate, and after being left at room temperature for 15 minutes, it was peeled off from the glass plate, dried in an oven at 80°C for 10 minutes, and dried at 120°C for 20 minutes, thereby obtaining a polymer film with a thickness of 40 μm and a glass transition temperature (Tg) of 140°C. The obtained polymer film has a light transmittance of 93% at a wavelength of 590 nm. In addition, the in-plane phase difference Re (590) of the above polymer film is 5.0 nm, and the phase difference Rth (590) in the thickness direction is 12.0 nm. The average refractive index is 1.576.
[0197] The obtained polymer film was uniaxially stretched to 1.5 times in an air circulation constant temperature oven at 150°C to obtain a retardation film F. The obtained retardation film F had Re(550) of 140 nm, Rth(550) of 140 nm, and Re(450) / Re(550) of 1.06.
[0198]
[0199] (Production of polarizing plate with phase difference layer and liquid crystal display device)
[0200] A polarizing plate with a phase difference layer was prepared in the same manner as in Example 1 except that the phase difference film F was used instead of the phase difference film A, and a liquid crystal display device was prepared in the same manner as in Example 1 except that the polarizing plate with a phase difference layer was used. The liquid crystal display device was made to display a white image, and visual confirmation through polarized sunglasses was evaluated in the white image state.
[0201] Table 1 shows the evaluation results.
[0202]
[0203] Industrial Applicability
[0204] The liquid crystal display device of the present invention can be suitably used in portable devices such as portable information terminals (PDAs), mobile phones, clocks, digital cameras, portable game consoles, office automation equipment such as computer monitors, notebook computers, copiers, video cameras, LCD televisions, microwave ovens and other household electrical appliances, rear-view displays, displays for car navigation systems, car audio and other in-vehicle equipment, display equipment such as information displays for commercial stores, security equipment such as surveillance displays, nursing displays, medical displays and other nursing and medical equipment, and the like.
[0205] Explanation of symbols
[0206] 10 Liquid crystal unit
[0207] 11 base plate
[0208] 12 substrate
[0209] 13 Liquid crystal layer
[0210] 20 First polarizer
[0211] 30 Second polarizer
[0212] 100 LCD Panel
[0213] 200 Phase difference layer (first phase difference layer)
[0214] 300 Backlight source
[0215] 400 Other phase difference layer (second phase difference layer)
[0216] 500 Liquid crystal display device
Claims
1. A liquid crystal display device comprising: A liquid crystal panel comprising a liquid crystal cell, a first polarizer disposed on a visual confirmation side of the liquid crystal cell, and a second polarizer disposed on a back side of the liquid crystal cell; A phase difference layer, which is disposed on a visual confirmation side of the liquid crystal panel; as well as a backlight source, the backlight source illuminating the liquid crystal panel from the back side, Wherein, the phase difference layer is formed of polycarbonate resin, The in-plane phase difference Re(550) of the phase difference layer is 100 nm to 180 nm and satisfies the relationship of Re(450)<Re(550)<Re(650). The angle between the slow axis of the phase difference layer and the long side of the liquid crystal panel is 35° to 55°. The backlight source has a discontinuous emission spectrum. The emission spectrum of the backlight source has a peak P1 in the wavelength region of 430 nm to 470 nm, a peak P2 in the wavelength region of 530 nm to 570 nm, and a peak P3 in the wavelength region of 630 nm to 670 nm. When the wavelength of peak P1 is set to λ1, the height is set to hP1 and the half-peak width is set to Δλ1, the wavelength of peak P2 is set to λ2, the height is set to hP2 and the half-peak width is set to Δλ2, the wavelength of peak P3 is set to λ3, the height is set to hP3 and the half-peak width is set to Δλ3, the height of the valley between peaks P1 and P2 is set to hB1, and the height of the valley between peaks P2 and P3 is set to hB2, they satisfy the following relationship equations (1) to (3): 1.10≤(λ2-λ1) / (Δλ2+Δλ1)≤1.50 (1) (λ3-λ2) / (Δλ3+Δλ2)>1 (2) 0.8≤{hP2-(hB2+hB1) / 2} / hP2≤1 (3).
2. The liquid crystal display device according to claim 1, wherein: The refractive index ellipsoid of the phase difference layer shows a relationship of nx>nz>ny, and the Nz coefficient is 0.2 to 0.
8. 3 . The liquid crystal display device according to claim 1 , further comprising another retardation layer whose refractive index ellipsoid shows a relationship of nz>nx≥ny between the liquid crystal panel and the retardation layer.
4. The liquid crystal display device according to claim 1, wherein: The backlight source comprises a red LED, a green LED and a blue LED, and the phosphor of the red LED is activated by tetravalent manganese ions.
5. The liquid crystal display device according to claim 1, wherein: The backlight source includes a blue emitting LED and a wavelength conversion layer including quantum dots.
6. The liquid crystal display device according to claim 1, wherein: The absorption axis of the first polarizer is substantially orthogonal or parallel to the long side of the liquid crystal panel, the absorption axis of the second polarizer is substantially orthogonal or parallel to the long side of the liquid crystal panel, and the absorption axis of the first polarizer is substantially orthogonal to the absorption axis of the second polarizer.
Citation Information
Patent Citations
JP1975083482A
Production of stretched film or sheet
JP1990113920A
Stretched film and its formation
JP1991182701A
Production of stretched film and phase difference plate
JP2000009912A
Protective film for polarizer and its manufacturing method
JP2001343529A